A GIS based screening tool for locating and ranking of suitable stormwater harvesting sites in urban areas - Inamdar, P.; Cook, Simon; Sharma, A.; Corby, N.; O'Connor, J.; Perera, B. (Academic Press, 2013)
There is the need to re-configure current urban water systems to achieve the objective of sustainable water sensitive cities. Stormwater represents a valuable alternative urban water source to reduce pressure on fresh water resources, and to mitigate the environmental impact of urban stormwater runoff. The selection of suitable urban stormwater harvesting sites is generally based on the judgement of water planners, who are faced with the challenge of considering multiple technical and socio-economic factors that influence the site suitability. To address this challenge, the present study developed a robust GIS based screening methodology for identifying potentially suitable stormwater harvesting sites in urban areas as a first pass for then more detailed investigation. The study initially evaluated suitability based on the match between harvestable runoff and demand through a concept of accumulated catchments. Drainage outlets of these accumulated catchments were considered as potential stormwater harvesting sites. These sites were screened and ranked under screening parameters namely demand, ratio of runoff to demand and weighted demand distance. The methodology described in this paper was successfully applied to a case study in Melbourne, Australia in collaboration with the local water utility. The methodology was found to be effective in supporting the selection of priority sites for stormwater harvesting schemes, as it provided the basis to identify, short-list and rank sites for further detailed investigation. The rapid identification of suitable sites for stormwater harvesting can assist planners in prioritising schemes in areas that will have the most impact on reducing potable water demand. © 2013 Elsevier Ltd.